Meningkatkan Kesiapsiagaan Bencana Kebakaran melalui Media Maket Jalur Evakuasi pada Siswa Berkebutuhan Khusus di Sekolah Khusus YKDW 03 Kota Tangerang - Hasrian Hasrian; Achmad Nurfikri Alamsyah; Ahmad Aldizar Akbar; Mohamad Rizky Muyassar; M.Aji Bimantara; Fathin Aulia Rahman; Didik Hariyadi Raharjo (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service activity aimed to improve fire disaster preparedness among students with special needs at SKH YKDW 03 School in Tangerang City through the use of evacuation route mock-up media. The main issue addressed was the students' low understanding of evacuation procedures in the event of a fire at school. The methods employed included training and simulation, consisting of disaster preparedness education, training on the use of the evacuation mock-up, and direct simulation within the school environment. Pre-test and post-test results showed that the use of evacuation route mock-ups was effective in enhancing disaster preparedness among students with special needs at YKDW 03 Special School. Significant improvements were observed in evacuation route comprehension, simulation participation, and students’ sense of safety during the activity. This approach proves to be a relevant, inclusive, and adaptive disaster education strategy for students with physical and sensory disabilities. The activity also encourages the integration of mock-up media into regular learning and ongoing training for teachers and staff